2020
DOI: 10.3844/ajassp.2020.204.213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Toxic Effects of Chitosan-Coated Magnetite Nanoparticles on Drosophila melanogaster

Abstract: Nanoparticles are a cause for concern because of their potential toxic effects on human health and the environment. The aim of this study was to assess the toxic effect of chitosan-coated magnetite nanoparticles (11.00±4.7 nm) on Drosophila melanogaster through the observation of hemolymph composition, DNA damage, larval survival and lifespan of flies. Chitosan-coated magnetite nanoparticles were synthesized by coprecipitation method. Drosophila larvaes and adults were exposed to 500 and 1000 ppm nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
5
2
Order By: Relevance
“…In the present study, the tested nanomaterials alone have no toxicity against S. littoralis stages; these ndings much agree with the ndings which found that no signi cant genotoxicity or cytoxicity existed in magnetic nanoparticles (MNPs) treated water, where, MNPs have great potential in practical drinking water treatment to remove pathogenic bacteria 52 . On the other hand, some studies disagree with the present results which clari ed that exposure to a highly concentrated dose of Ch-Fe3O4NPs leads to high larva mortality 53 . Previous research works have reported acute intoxication of Drosophila melanogaster with iron (FeSO4) and proved to diminish y survival and locomotor activity, including climbing capabilities 54 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, the tested nanomaterials alone have no toxicity against S. littoralis stages; these ndings much agree with the ndings which found that no signi cant genotoxicity or cytoxicity existed in magnetic nanoparticles (MNPs) treated water, where, MNPs have great potential in practical drinking water treatment to remove pathogenic bacteria 52 . On the other hand, some studies disagree with the present results which clari ed that exposure to a highly concentrated dose of Ch-Fe3O4NPs leads to high larva mortality 53 . Previous research works have reported acute intoxication of Drosophila melanogaster with iron (FeSO4) and proved to diminish y survival and locomotor activity, including climbing capabilities 54 .…”
Section: Discussioncontrasting
confidence: 99%
“…The tested magnetic nanomaterials decreased the insecticidal effect of cyromazine and have antagonistic effect, this result agreed with Saeidi et al 55 , who approved the unique adsorption properties of the magnetic nanomaterials that due to different distributions of reactive surface sites and disordered surface regions that may explain the antagonistic effect of the tested nanomaterials. The dose concentration of Ch-Fe3O4NPs showed shortening of lifespan and decreased larval survival associated with the toxic effect against larvae and adults of D. melanogasterr 53 . Abraham et al 33 studied the effects of Fe3O4 nanoparticles during the development of the tephritid ies C. capitata and A. fraterculus.…”
Section: Discussionmentioning
confidence: 97%
“…littoralis stages; these findings much agree with the findings which found that no significant genotoxicity or cytotoxicity existed in MNP-treated water, where MNPs have great potential in experimental drinking water treatment to remove pathogenic bacteria . On the other hand, some studies disagree with the present results, which clarified that exposure to a highly concentrated dose of Ch-Fe 3 O 4 NPs leads to high larval mortality . Previous research works have reported acute intoxication of Drosophila melanogaster with iron (FeSO 4 ) and proved to diminish fly survival and locomotor activity, including climbing capabilities …”
Section: Discussioncontrasting
confidence: 91%
“…60 On the other hand, some studies disagree with the present results, which clarified that exposure to a highly concentrated dose of Ch-Fe 3 O 4 NPs leads to high larval mortality. 61 Previous research works have reported acute intoxication of Drosophila melanogaster with iron (FeSO 4 ) and proved to diminish fly survival and locomotor activity, including climbing capabilities. 62 The use of tested nanomaterials as an additive compound to the insecticide aims to reduce the insecticide dosage and thus reduce the impact on the environment by increasing its effectiveness, not by increasing the insecticide toxicity but by interfering with the other aspects of the pest, such as the biological, behavioral, and physiological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Fe 3 O 4 NPs were synthesized using a coprecipitation method [ 50 ]. A 50 mL solution containing 0.30 g of FeCl 3 ·6H 2 O (97%, Loba Chemie Mumbai, India) and 0.14 g of FeCl 2 ·4H 2 O (98%, BDH Chemicals, London, UK) was prepared.…”
Section: Methodsmentioning
confidence: 99%